p.G360R is a pathogenic GLA gene mutation responsible for a classic phenotype of Fabry disease - Carvalho Silva, Daniela (2020)
The authors report the case of a classic phenotype of Fabry disease in a 60-year-old male patient presenting with left ventricular hypertrophy and stroke. Genetic analysis revealed 2 GLA-gene variants, i.e., p.R356Q and p.G360R. This clinical case highlights that the finding of 2 or more GLA gene variants in a Fabry patient should lead to a careful evaluation in order to determine their exact role in the condition. This case also provides the first clinical evidence that the p.G360R mutation is pathogenic and responsible for a classic phenotype of Fabry disease. The clinical improvement following the initiation of enzyme replacement therapy reinforces the importance of Fabry disease awareness and diagnosis in patients exhibiting red flags, such as left ventricular hypertrophy and stroke.